Karakter Pertumbuhan dan Aktivitas Nitrifikasi Kultur Mikroba N-Sw - Agustiyani, Dwi; Imamuddin, Hartati; Haryanto, Tanto (Perhimpunan Biologi Indonesia, 2008)
ABSTRACTThe growth character and nitrification activity of nitrifying cultures (N-Sw). Theculture of nitrifiers (N-Sw) was obtained from acclimated sludge of sawit palm oil industrywastewater. The growth and nitrification activity of those cultures were investigated.The result shows that the growth and nitrification activity attained optimum at pH 7-8,and temperature of 30 0C. The culture of nitrifiers was still growing at pH 5, but thenitrification activity was not detected. The growth of nitrifiers and the nitrification activitywas inhibited at 40 0C. The ammonium conversion rate reached 0,088-0,090 mg NNH4+/L/hour/g biomass. The rate of ammonium conversion in the bioreactor increasedto 0.630 mg N-NH4+/L/hour/g biomass as the pH maintained at 7.5-8 and dissolvedoxygen at 3-4 mg/l O2.Key words: nitrifying culture, ammonium, ammonium convertion rate